Antibodies against Porphyromonas gingivalis in serum and saliva and their association with rheumatoid arthritis and periodontitis. Data from two rheumatoid arthritis cohorts in Sweden - Svärd, Anna; Kastbom, Alf; Ljungberg, Karin Roos; Potempa, Barbara; Potempa, Jan; Persson, G. Rutger; Renvert, Stefan; Berglund, Johan Sanmartin; Söderlin, Maria K. (Frontiers in Immunology, 2023)
Background Periodontitis and oral pathogenic bacteria can contribute to the development of rheumatoid arthritis (RA). A connection between serum antibodies to Porphyromonas gingivalis (P. gingivalis) and RA has been established, but data on saliva antibodies to P. gingivalis in RA is lacking. We evaluated antibodies to P. gingivalis in serum and saliva in two Swedish RA studies, and their association with periodontitis, antibodies to citrullinated proteins (ACPA) and disease activity. Methods The Secretory Antibodies in Rheumatoid Arthritis (SARA) study included 196 RA patients and 101 healthy controls. The Karlskrona RA study, a population-based cross-sectional study, includes 132 dentate RA patients > 61 years of age, who underwent rheumatological and dental examinations. Serum IgG and IgA antibodies and saliva IgA antibodies to the P. gingivalis-specific R-gingipain B (RgpB) were measured in all RA patients and controls. Results The mean level of saliva IgA anti-RgpB antibodies was higher among RA patients (45 AU/mL) than among healthy controls (13 AU/mL) (p<0.001). This was confirmed in multivariate analysis. Anti-RgpB antibodies did not correlate with disease activity in multivariate analyses. Anti-RgpB antibodies were not associated with periodontitis or serum IgG ACPA. Conclusion RA patients had higher levels of saliva IgA anti-RgpB antibodies than healthy controls. Anti-RgpB antibodies were not associated with periodontitis, serum IgG ACPA or disease activity. Our results indicate a local production of IgA anti-RgpB in the salivary glands that is not accompanied by systemic antibody production.